Soils of Kwazulu-Natal and Mpumalanga : recognition of natural soil bodies - Laker, M.C. (Michiel Christiaan), 1939- (University of Pretoria, 2013)
Thesis (PhD (Soil Science))--University of Pretoria, 2007.